Effects of soil compaction, temperature, and moisture on the development of the Fusarium root rot complex of pea in southwestern Ontario - Tu, J.C. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
The pea root rot complex (Fusarium spp.) is known to be affected by compaction, temperature, and moisture of the soils. This paper reports the effects of these factors on root rot severity and pea (Pisum sativum) growth tested in a controlled environment, using a Fusarium-infested soil collected from a field with a severe root rot history. For each factor, several increments were used. The results showed that in a controlled environment, an increase in soil bulk density due to compaction significantly increased root rot incidence and disease severity, and drastically reduced the fresh weight of pea plants. Stepwise increases in soil temperature from 10 to 30°C resulted in increases in estimated root rot severity and foliar symptom expression. Pea plants grown in soil moisture at 75% of field capacity had significantly lower Fusarium root rot incidence and severity than those grown in soil at 100%, 50% or 25% of field capacity. Pea plants subjected to temporary flooding exhibited an increased root rot incidence and severity as the duration of flooding increased from 1 to 5 d.